Relevansi Pemikiran Muhammad Iqbal Dalam Pembentukan Karakter Siswa Di Era Millenium - Zakiyah Kholidah (TA'LIM : Jurnal Studi Pendidikan Islam, 2018)
Muhammad Iqbal is a great scholar from India who influences the Islamic world, one of whose attention is on character education. To face the millennium era requires a strong and responsible person, and high motivation to achieve goals. A student who is still in a period of rapid development physically and mind easily affected from various things, both positive and negative. Therefore, a teacher must equip students with a character education with real and habitual examples. The result of character education habituation becomes the guidance of students in facing a challenging future and many changes. Seeing the condition of students in many countries of Indonesia are exposed to the impact of technology and moral crisis to make various circles to give attention and salvation in various ways and methods. Muhammad Iqbal offers character education to save and prevent students from moral crisis is through the formation of characters in the form of exemplary, self-potential development of students, and fosters the attitude of tolerance.